Ethosuximide stabilizes sleep-related oscillations and reduces sleep fragmentation during alcohol withdrawal - Wiggins, Walter Francis (Wake Forest University, 2012)
The central focus of my dissertation is the study of the effects of ethanol on brain rhythms, measured by electroencephalography (EEG), as they pertain to alcohol withdrawal-related insomnia (AWI). AWI is an important clinical problem for chronic alcoholics undergoing treatment for alcoholism. The severity of AWI is highly correlated with increased risk of relapse. Furthermore, the current first-line therapy for alcohol withdrawal, chlordiazepoxide, is inappropriate for long-term management of AWI due to potential for abuse and negative side effects. While much of the research into the mechanisms underlying AWI has focused on mechanisms of global inhibition and excitation, more specific mechanisms of coordinated activity implicated in the maintenance of sleep are adversely affected by chronic alcohol use. The work described herein employs the chronic intermittent ethanol (CIE) vapor administration method in mice to study the effects of ethanol exposure and withdrawal on sleep and oscillations in neuronal activity between the thalamus and cortex (or thalamocortical oscillations). Sleep-related oscillations (SROs) in neuronal activity are a subset of thalamocortical oscillations that occur during the rapid eye movement (REM) and, more importantly, non-REM (NREM) stages of sleep. T-type calcium channels are an important component of the cellular processes that generate and maintain SROs. In two complementary studies, we examined the effects of ethosuximide (ETX), a purported T-type calcium current inhibitor, and genetic suppression of a T channel subtype on SROs and sleep in mice during ethanol exposure and withdrawal. In the first study, we observed reversal of withdrawal-mediated disruptions in SROs with ETX treatment, which we predicted would help stabilize sleep during withdrawal. In the second study, we observed increased stability of sleep during withdrawal in both ETX-treated and genetically modified mice. These results suggest, for the first time, an important role for T-type calcium channels in the treatment of AWI. Furthermore, these studies lay the groundwork for investigating the potential use of ETX, an FDA-approved drug with a minimal side effect profile, in the treatment of AWI.
Keywords: Alcohol withdrawal; Ethanol; Ethosuximide; Sleep; Sleep fragmentation; Sleep-related oscillations